Effect of carbon disulfide on pyrogallol-luminol auto-oxidation chemiluminescence system and superoxide anion - Jian, Le; Chen, Q. (Chinese Medical Association, 2000)
OBJECTIVE: To study the effect of carbon disulfide (CS(2)) on pyrogallol-luminol auto-oxidation chemiluminescence (PA-L) system and production of superoxide anion. METHODS: Luminescence dynamic curve of CS(2) and inhibition effect of superoxide dismutase (SOD) on intensity of chemiluminescence induced by CS(2) were studied with PA-L chemiluminescence system. RESULTS: Different concentrations of CS(2) (10, 40, 80 mg/ml) could enhance the emission intensity of chemiluminescence of PA-L system and delayed its peak time, with a significant dose-effect relationship, as compared with that of solvent ethanol. Peak of chemiluminescence induced by 80 mg/ml of CS(2) was higher than its background value without solvent ethanol. Chemiluminescence induced by CS(2) could be inhibited by SOD. CONCLUSION: CS(2) can generate superoxide anion in PA-L system and delay the peak time of chemiluminescence emission dynamic curve.